The Safe and Effective Use of Lumbar Epidural for the Surgical Management of a Femoral Neck Fracture in a Patient with Progressed Amyotrophic Lateral Sclerosis (ALS): A Case Report - Anthony, Mina; Jurcik, Charlota; Korban, Anna; Discepola, Patrick; Anthony, Christy; Kwon, Minho; Eloy, Jean Daniel (International Journal of Innovative Research in Medical Science, 2019)
Objective: Because of the limited publications on the appropriate anesthetic management of patients with Amyotrophic Lateral Sclerosis (ALS), this manuscript is a means of providing outcome data on the use of epidural anesthesia in an ALS patient and to discuss the risks and benefits of neuraxial anesthesia in these individuals. Background: ALS is a debilitating neuromuscular disease that arises from destruction of large upper and lower motor neurons. Patients develop weakness of their peripheral muscles that can progress to include intrinsic muscles of the airway and oropharynx, which creates a challenge when determining the safest anesthetic plan and considerations for the post-operative course. Case: The case discusses a 78-year-old female with a longstanding history of ALS, for which she required noninvasive mechanical ventilatory support and gastrostomy tube feedings secondary to oropharyngeal and upper respiratory muscle weakness and atrophy. The patient presented for orthopedic repair of a femoral fracture. She underwent epidural anesthesia successfully without any exacerbation of her lower extremity weakness. Conclusion: Regional anesthesia in ALS patients appears to be a safe means of delivering intraoperative anesthesia and postoperative analgesia without compromising baseline functional status. This may be a superior technique to general anesthesia and endotracheal intubation, particularly in patients who already suffer from dysphagia and respiratory compromise.